Rotavirus Vaccine and Health Care Utilization for Diarrhea in U.S. Children - Cortes, Jennifer E; Curns, Aaron T; Tate, Jacqueline E; Cortese, Margaret M; Patel, Manish M; Zhou, Fangjun; Parashar, Umesh D (The New England journal of medicine, 2011)
Routine U.S. infant vaccination for rotavirus began in 2006. CDC investigators found that rates of diarrhea-associated hospitalization, outpatient visits, and ER visits declined in 2007–2009 as compared with 2001–2006 among children under 5. The benefit was greater for vaccinated children. Before February 2006, when routine vaccination of infants in the United States with pentavalent rotavirus vaccine (RV5) was recommended, rotavirus diarrhea caused an estimated 400,000 visits to physician's offices, 200,000 emergency department visits, 55,000 hospitalizations, and 20 to 60 deaths annually among children under 5 years of age in the United States, for an annual total medical cost of approximately $300 million. 1 , 2 RV5 is administered orally in children in three doses, one each given at 2, 4, and 6 months of age. 3 , 4 In trials, use of RV5 reduced the incidence of rotavirus-related hospitalizations or emergency department visits by . . .